Successful Treatment of Human Plague with Oral Ciprofloxacin - Apangu, Titus; Griffith, Kevin; Abaru, Janet; Candini, Gordian; Apio, Harriet; Okoth, Felix; Okello, Robert; Kaggwa, John; Acayo, Sarah; Ezama, Geoffrey; Yockey, Brook; Sexton, Christopher; et al. (Emerging infectious diseases, 2017)
The US Food and Drug Administration recently approved ciprofloxacin for treatment of plague (Yersina pestis infection) based on animal studies. Published evidence of efficacy in humans is sparse. We report 5 cases of culture-confirmed human plague treated successfully with oral ciprofloxacin, including 1 case of pneumonic plague.
Keywords: Treatment; Human Plague; Oral Ciprofloxacin